Using the ABCD2 Scale and Other Risk Factors to Predict the Risk of Permanent Stroke after Temporary Stroke. (Texas Journal of Medical Science, 2023)
A temporary ischemic attack (TIA) is described as an immediate loss of localized cerebral and ocular function that lasts for 24 hours and is thought to be caused by embolic or coagulant vascular disease after thorough evaluation. Objective: our study examined the role of ABCD2 alongside additional risk variables in the capacity to predict the development of TIA to stroke. Methods: Cross-sectional research was conducted over a 12-month period, from 12 January 2021 to 24 September 2022, at the emergency department of Baghdad Teaching Hospital, Medical City Complex, which is Baghdad, Iraq. The Department of Emergency Medicine at Baghdad Teaching Hospital and the Emergency Medicine Council on the Arab Board approved the study protocol, which includes a questionnaire for gathering information about the population of interest (name, age, occupation, address, medical condition, smoking, drug use, weight gain, symptoms and signs, examinations, and all medical records) and the outcomes that were considered. The selection of patients was based on the criteria for inclusion and exclusion that were determined. Before including any patients in the study, verbal agreement was acquired from each one of them. Results: In this study, 150 stroke patients were included, of whom 94 (62.7%) had no subsequent transient ischemic attack (TIA), and 56 (37.3%) did. According to the study, stroke struck 30 TIA patients (53.6%) in less than a week as opposed to 26 (46.4%) in a period of seven days or more (P 0.001). Conclusion: Stroke is more likely to occur in TIA patients who have ABCD2 values of greater than three during seven days of the TIA. In this study, we discovered a strong relationship between weight and a high ABCD2 score as opposed to a low score. The number of antihypertensive medications has also been linked to a high ABCD2 score, which is independently linked to an increased likelihood of stroke post-TIA.